Manganese‐Catalyzed Electrochemical Diazidation of Dehydroalanine Peptides - Xinwei Hu; Chengwei Zheng; Xiaotong Song; Balati Hasimujiang; Mu Chen; Zhixiong Ruan (Advanced Science)
Abstract Dehydroalanine (Dha), a readily introducible non‐canonical amino acid, is widely used for protein post‐translational modification (PTM) and site‐specific labeling of peptides and proteins. Despite its growing applications in biological systems, the precise modification of unnatural amino acid peptides and their conversion into functionalized endogenous peptides remain underdeveloped. To address this challenge, a novel peptide modification strategy is developed based on a manganese‐catalyzed electrochemical radical relay process between dehydroalanine peptides and sodium azide. This method demonstrates excellent functional group tolerance, accommodating amino acids with sensitive groups and even drug molecules, achieving yields of up to 99%. Mechanistic studies reveal that the reaction proceeds via a Mn(II)‐mediated electrochemical generation of azidyl radicals (N3⚫), which undergo regioselective addition to the Dha moiety, enabling efficient and site‐selective diazidation. The rapid diazidation strategy presented here provides a robust and efficient approach for converting unnatural amino acids into functionalized endogenous peptides, offering significant potential for applications in peptide chemistry and bioconjugation.